Diversity and prevalence of Salmonella spp. in gulls caught at a landfill, Zagreb, Croatia - Ječmenica, Biljana; Humski, Andrea; Taylor, Louie Thomas; Šimpraga, Borka; Krstulović, Fani; Amšel Zelenika, Tajana; Jurinović, Luka (Veterinarska stanica, 2023)
Gulls are a group of seabirds distributed worldwide that are an important reservoir of Salmonella spp. Salmonellosis is the second most commonly reported gastrointestinal infection in humans, and understanding the role wild birds have in spreading Salmonella can help to improve the health of humans and domestic animals. The mobility and migration capacity of gulls makes them an interesting group for research given their potential role in spreading pathogens. This paper presents the diversity and prevalence of Salmonella spp. in different gull species caught at a landfill in Zagreb in the winter months over a nine-year period from 2014-2022. In total, 1083 cloacal swabs were sampled from six gull species: Black-headed Gull (Larus ridibundus), Yellow-legged Gull (L. michahellis), Caspian Gull (L. cachinnans), Common Gull (L. canus), Lesser Black-back Gull (L. fuscus) and Herring Gull (L. argentatus). The prevalence of Salmonella was 5.82%, and 16 Salmonella serotypes were identified; S. Typhimurium had the highest prevalence (47.62%) followed by S. Enteritidis (12.69%) and S. Infantis (9.52%). To date, 82 Salmonella serotypes have been isolated in research on gulls in Europe, with S. Typhimurium as the most common, followed by S. Agona and S. Enteritidis. In this study, we found three serotypes not previously reported in gulls, S. Yalding, S. Reading and one with the antigenic formula O:17; H:z10; H:e,n,x,z15 (IIIb). Galebovi su skupina morskih ptica raširenih diljem svijeta koje su važan rezervoar Salmonella spp. Salmoneloza je druga najčešće prijavljena gastrointestinalna infekcija u ljudi i razumijevanje uloge koju divlje ptice imaju u širenju Salmonella spp. može pomoći u poboljšanju zdravlja ljudi i domaćih životinja. Mobilnost i migracijska sposobnost čini galebove vrlo zanimljivom skupinom za istraživanje zbog njihove potencijalne uloge u širenju patogena. Kroz ovaj rad prikazujemo raznolikost i prevalenciju Salmonella spp. kod nekoliko vrsta galebova ulovljenih na odlagalištu otpada tijekom zime u ...